The Effects of Cognitive Flexibility on Teacher’s Readiness To Implement the Merdeka Curriculum - Idawati, Idawati; Akrom, Abdul Hayyi; Asy’ari, M. Hasanil (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2024)
This article aims to determine cognitive flexibility in influencing teacher readiness for implementing the